2015
DOI: 10.3332/ecancer.2015.539
|View full text |Cite
|
Sign up to set email alerts
|

Genetic susceptibility in childhood acute leukaemias: a systematic review

Abstract: Acute leukaemias (AL) correspond to 25–35% of all cancer cases in children. The aetiology is still sheltered, although several factors are implicated in causality of AL subtypes. Childhood acute leukaemias are associated with genetic syndromes (5%) and ionising radiation as risk factors. Somatic genomic alterations occur during fetal life and are initiating events to childhood leukaemia. Genetic susceptibility has been explored as a risk factor, since environmental exposure of the child to xenobiotics, direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 101 publications
1
34
0
Order By: Relevance
“…These mice also show a defect in kidney development, craniofacial abnormalities, and delayed endochondral ossification which results in growth retardation . Besides the functions on cell differentiation, many investigations reveal that the ARID5B gene mutation is associated with oncogenicity of B‐cell acute leukemia and endometrial cancer . ARID5B binds to the histone demethylase, plant homeodomain finger two (PHF2), which demethylates the repressive H3K9me2, resulting in activation of transcription .…”
Section: Introductionmentioning
confidence: 99%
“…These mice also show a defect in kidney development, craniofacial abnormalities, and delayed endochondral ossification which results in growth retardation . Besides the functions on cell differentiation, many investigations reveal that the ARID5B gene mutation is associated with oncogenicity of B‐cell acute leukemia and endometrial cancer . ARID5B binds to the histone demethylase, plant homeodomain finger two (PHF2), which demethylates the repressive H3K9me2, resulting in activation of transcription .…”
Section: Introductionmentioning
confidence: 99%
“…Carbon source metabolism in acute myeloid leukaemia: gene × micro-environment interactions G × E interaction studies have been proposed in some haematological malignancies [177]. Despite the absence of well defined G × E interactions, recent findings indicate that acute myeloid leukaemia (AML) may represent a valid study case for G × micro-E interactions, and help design novel specific therapies.…”
Section: Tumour Heterogeneity As the Basis For Acquired Resistance Inmentioning
confidence: 99%
“…Several studies have reported that genes in xenobiotic pathways, such as CYP2E1, GSTM1, NQO1, NAT2, and MDR1, influence the risk of childhood leukemia alone or in combination with chemical exposures. 30 Here, we provide examples of risk factors for childhood leukemia with strong levels of evidence to date, and for which preventive measures can be implemented at the individual level through information to families and health care providers or, at the population-level, leveraging existing programs and resources.…”
Section: Current Knowledge On "Actionable" Risk Factors Of Childhood mentioning
confidence: 99%
“…Also, studies taking into account genetic polymorphisms in metabolic pathways reported that CYP1A1 variants an GSTM1 deletion may modify the effect of in utero exposure to tobacco smoking. 30,51 Although the debate is still open regarding the impact of maternal smoking on the risk of childhood leukemia, stronger evidence is accumulating for the role of paternal smoking as reported in several individual studies and meta-analyses of ALL. 48,50,52,53 In a study examining the effect of paternal smoking by period of exposure, elevated risks of childhood ALL were observed only when fathers reported smoking both before and after birth (and not those smoking only before birth or only after birth), 54 suggesting that preand postnatal cellular insults were necessary steps, consistent with the 2-hit model of leukemogenesis.…”
Section: Tobacco Smokingmentioning
confidence: 99%